Whether the Effect of Sperm DNA Fragmentation on the Clinical and Laboratory Outcomes Changes with the Paternal age in the intracytoplasmic sperm injection Cycles of Donor Oocytes - Repalle, Deepthi; kv, saritha; Bhandari, Shilpa; Choudhary, Jitendra (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: The present study aimed to know the effect of paternal age together with Sperm DNA fragmentation on the clinical and laboratory outcomes in the donor oocyte intracytoplasmic sperm injection cycles. STUDY DESIGN: In this prospective cohort study a total of 229 patients undergoing their first intracytoplasmic sperm injection cycles and fresh blastocyst embryo transfer with donor oocytes were included in this study. All the patients of the donor oocyte intracytoplasmic sperm injection cycles were categorized into four groups based on the male age and sperm DNA fragmentation. Ⅰ. Y group (Young, Male age <40 years) with low sperm DNA fragmentation (Sperm DNA fragmentation ≤30%), Ⅱ. Y group (Young, Male age <40 years) with high sperm DNA fragmentation, Ⅲ. Advanced paternal age group, Male age ≥40 years with low sperm DNA fragmentation (sperm DNA fragmentation≤30%), and Ⅳ. Advanced paternal age group, Male age ≥40 years) with high sperm DNA fragmentation (sperm DNA fragmentation>30%). RESULTS: Clinical, as well as laboratory outcomes, were correlated among these four groups. There was no significant difference in the clinical outcomes among the groups, whereas coming to the laboratory outcomes, the advanced paternal age group with high sperm DNA fragmentation has significantly decreased good quality embryos (Grade A) at day 3 rate, blastocyst rate, and good quality blastocyst rate compared to other groups (p<0.05). CONCLUSION: In conclusion, advancing paternal age together with high sperm DNA fragmentation has no deleterious effect on the clinical outcomes in the intracytoplasmic sperm injection cycles of donor oocytes.